A Greener Alternative Titration Method for Measuring Acid Values of Fats, Oils, and Grease. (27th August 2019) - Zhang, Junsong; Lu, Mingming; Ren, Fumin; Knothe, Gerhard; Tu, Qingshi
Abstract: A greener alternative method is proposed for measuring acid values (AV) of fats, oils, and grease (FOG) based on visual titration. Compared with Official Method Cd 3d‐63 of the American Oil Chemists' Society (AOCS), this greener alternative method can eliminate the use of toluene, which in turn reduces toxicity and cost. A total of 44 samples of yellow and brown grease with AV ranging from 0.13 to 170.37 (mg KOH) g −1 were titrated using both methods. The alternative titration method can provide accurate and reliable results to determine the AV of FOG by various statistical analyses including repeatability, linear regression, f ‐test, t ‐test, and method accuracy calibration with AOCS Cd 3d‐63. This low‐cost method can be recommended for routine titration in research and development, and in biodiesel plants for most FOG samples.